Exploring Riot Policing Strategies: The Practice of Indonesian National Police in Handling Riot - Mohammad Rizky Zulfikar; Desideria Cempaka Wijaya Murti (Eduvest - Journal of Universal Studies, 2026)
The Indonesian National Police (INP) has the primary tasks of maintaining public safety, enforcing the law, and serving the community. However, numerous incidents have damaged the INP’s public trust and legitimacy, one of which is the excessive use of force in riot policing. This study aims to examine the INP’s riot policing strategies, with specific objectives to explore the current strategies employed by the INP, assess key areas for improvement, and provide recommendations based on the identified strategic priorities. This research employs a qualitative method through in-depth interviews. The analysis concludes that the INP’s riot policing strategy requires evaluation due to its reliance on reactive policing. The key strategies proposed to enhance the INP’s effectiveness in riot policing include the use of accurate intelligence data, improved human resource management, strengthened accountability mechanisms, and the integration of technology in both tactics and operational management. Furthermore, establishing effective rapport and communication between different layers of protesters is also essential for improving outcomes in riot management.